Classical sociological theory - Calhoun, Craig J. , 1952- (Chichester, West Sussex, UK : John Wiley & Sons, 2012)
This comprehensive collection of contemporary sociological theory is the definitive guide to current perspectives and approaches in the field, examining key topics and debates in the field
1. Micro-sociological analysis -- 2. Exchange and rationality -- 3. Institutions and networks -- 4. Power and inequality -- 5. The sociological theory of Michel Foucault -- 6. The sociological theory of Pierre Bourdieu -- 7. Race, gender, difference -- 8. Sociological theory of Jürgen Habermas -- 9. Modernity -- 10. Crisis and change
Complements Classical sociological theory
Includes bibliographical references and index
Keywords: Sociology -- History -- 20th century; Sociology -- Philosophy